EFEKTIVITAS PEMBERIAN PROGRAM HIBAH PENGEMBANGAN PERGURUAN TINGGI SWASTA (PHP-PTS) DALAM MENINGKATKAN INTELLECTUAL CAPITAL (IC) SEBAGAI SALAH SATU INTANGIBLE ASSET PERGURUAN TINGGI - INDRA LILA KUSUMA; MAYA WIDYANA DEWI (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2016)
This study aims to determine the effectiveness of program development grant private universities in all private colleges beneficiary PHP-PTS in Surakarta in 2013 thatdilihay of variable intellectual capital as an intangible asset that is part of the college tridharma. The sampling technique in this study using census method is to take all the members of the population (PTS beneficiary PHP-PTS in the region Surakarta). This study is a descriptive study using data collection techniques through observation (secondary data collection methods). While the data analysis using quantitative descriptive analysis techniques. The results showed that the use of funds PHP-PTS in improving IC is one of the intangible assets of the college has done very effectively by PTS who get these grants.